Implementasi Kebijakan Program Akselerasi di Madrasah Aliyah Unggulan Amanatul Ummah Pacet Mojokerto - Barnoto, Barnoto (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2016)
The focus of this study is the policy of accelerated programs in Madrasah Aliyah (MA) Amanatul Ummah Mojokerto that facilitates very smart children or talented children. The results of the study are as follows: (1) the program is conducted through socialization, coordination and consultation, while the models of policy plans are deliberative and strategic models; (2) the policy of accelerated programs in MA Amanatul Ummah Mojokerto are implemented by appointing an implementation team and applying a strict recruitment system for acceleration class. The pattern of building an institution brand image through the accelerated program is performed by the kiai and headmaster as a public figure; (3) evaluation of the policy is carried out externally by the Ministry of Religious Affairs at provincial and district levels, whose duty is to supervise and facilitate the implementation of the program, while internal evaluation is performed by the staffs and coordinators who directly conduct evaluation in the field. The types of evaluation of the accelerated program consist of result evaluation and process evaluation